Mechanical design, integration and optimization of mounting devices or mechatronic systems for a high-rise robot - Tan, Yong Kun (2017)
With advancement in terms of technology, many processes and tasks had been automated, especially in those industries that use the robotic system in their company or factory. Fully autonomous robot application has been realized since the second half of 20 centuries and increasingly in demand. For robots to operate and deal with those challenging and unpredicted obstacles, advanced equipment like sensors or scanners should be used to obtain the information around the robots before making the decision for the next step. Thus, proper installation or mounting of those sensors and scanners onto the robot is one of the key points to increase the efficiency of the robot. This report will be focusing on the process in design and development of a mounting platform catered to enhance the capability of the two-dimensional laser scanner especially operating in an environment that requires a height that is up to 10 meters. Processes such as initial concepts feasibility evaluation and exploration of the mounting method were done to select the ideal and most efficient mounting method. Design development enables the author to improve on the initial design and modify it to fit according to the specifications and practicality. Solidworks is used to illustrate the final form of the design in forms of 3D model and finite element analysis method is carried out to provide theoretical assurance on the structure integrity to substantiate the proposal for fabrications. It serves as an important documentation not only for the further development of the automatic high-rise spray painting robot but also important for other robotic systems with different functionality that will be used in different industry. By proper integration of scanning instrument onto the automatic robot, painting efficiency and accuracy could be enhanced.